2021
DOI: 10.1093/mnras/stab1834
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quasi-periodic oscillations in the long-term radio light curves of the blazar OT 081

Abstract: We report the detection of quasi-periodic oscillations (QPOs) in the radio light curves at 4.8, 8 and 14.5 GHz of the blazar OT 081, by means of the Weighted Wavelet Z-transform(WWZ) and Lomb-Scargle periodogram (LSP) methods. The LSP diagrams and time-averaged WWZ powers demonstrate several significant claims of QPOs above the 4σ confidence level: QPOs of ∼850 and ∼1500 days in the 4.8-GHz light curve, ∼850, ∼1120 and ∼1540 days in the 8-GHz light curve, ∼850 and ∼1130 days in the 14.5-GHz light curve. The Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 60 publications
0
20
1
Order By: Relevance
“…Through the above three formulas, the fractional variability amplitude values of γ-ray and G band are F γ = 0.59 ± 0.02 and F G = 0.58 ± 0.02, respectively, which indicates that there is relatively significant variability in this case. Recently, Li et al (2021) reported that there might be a positive correlation between F var and frequency, but this phenomenon is not apparent here.…”
Section: Fractional Variabilitycontrasting
confidence: 62%
See 3 more Smart Citations
“…Through the above three formulas, the fractional variability amplitude values of γ-ray and G band are F γ = 0.59 ± 0.02 and F G = 0.58 ± 0.02, respectively, which indicates that there is relatively significant variability in this case. Recently, Li et al (2021) reported that there might be a positive correlation between F var and frequency, but this phenomenon is not apparent here.…”
Section: Fractional Variabilitycontrasting
confidence: 62%
“…Alternatively, QPO-like flux modulations might be related to a geometrical scenario with the relativistic motion of the enhanced emission (or blobs) along the helical path of a jet. This scenario has been invoked to explain QPOs in PKS 2247-131 (Zhou et al 2018), 3C 454.3 (Sarkar et al 2021, and OT 081 (Li et al 2021) recently. When the emitting blob is moving helically within the magnetized jet with a high bulk Lorentz factor (Γ), due to the relativistic effects, the periodic changes in the viewing angle θ cause the Doppler boosted emission to be periodically modulated.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We note that a common approach to derive PSDs of an unevenly sampled time series is the Lomb-Scargle periodogram (LSP; Lomb 1976;Scargle 1982), which is also frequently used in the literature (Rani et al 2009(Rani et al , 2010Bhatta et al 2016b;Sandrinelli et al 2016;Castignani et al 2017;Sandrinelli et al 2017;Gaur et al 2018;Gupta et al 2019;Żywucka et al 2020;Bhatta & Dhital 2020;Li et al 2021). However, with numerical simulation, we demonstrate in Appendix C that the LSP method does not reproduce the shape of the underlying power spectrum correctly down to the highest frequencies.…”
Section: Estimation Of the Spectral Shape: The Psresp Methodsmentioning
confidence: 99%